Improving Student Learning Outcomes in Geography Subjects by Applying a STAD Type Cooperative Learning Model Based on Animation in Class XI Social Studies SHS 4 Bengkalis - Lisa, Nur Ifa; Suasti, Yurni; Ernawati, Ernawati (International Journal of Educational Dynamics, 2024)
Teachers utilizing a contextual approach are expected to integrate the material taught with real-world situations relevant to students' lives. Despite limitations in their abilities, teachers are still tasked with optimizing the learning process. The animation-based Student Teams Achievement Divisions (STAD) model facilitates an engaging and enjoyable learning environment. This approach allows students to naturally interact with the material, promoting direct practice in group settings. Contextual learning fosters a deeper understanding of the essence, meaning, and benefits of education, motivating students to persistently seek knowledge and develop a genuine enthusiasm for learning. Such conditions emerge when students comprehend their life needs and devise strategies to fulfill them. The study concludes that implementing the STAD cooperative learning model for Class XI IPS students at SHS 4 Bengkalis during the 2022/2023 academic year significantly enhanced learning outcomes. The pre-cycle completion rate was 50% (13 students), increasing to 73% (19 students) in Cycle I, and reaching 88% (23 students) in Cycle II. In terms of absorption rates, the initial figure was 67%, which rose to 73% in Cycle I and improved further to 86% in Cycle II. These results demonstrate the effectiveness of STAD in improving student engagement and achievement.